Expected time to recruitment in a single grade manpower system with two thresholds - Sridharan, J.; Saivarajan, A.; Srinivasan, A. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, a single graded marketing organization which is subject to loss of manpower due to its policy decisions is considered. A mathematical model is constructed using an univariate recruitment policy based on the shock model approach involving two thresholds (one is optional and the another one is mandatory) via order statistics for interdecision time. The performance measures of the time to recruitment are obtained. Also the new findings are verified with numerical illustration.